Desafios para a transição agroecológica no arco de desmatamento da Amazônia : estudo de caso no assentamento entre Rios - MT - Alvares, Suzana Marques Rodrigues (2012)
There is a critical situation for settlements, in terms of land reform, that can be seen by the great number of people abandoning their lands in the big areas with deforest and bonfire in Amazon. The present dissertation intended to analyze the Agroecological Transition Process in Entre Rios Settlement which was driven forward by PADEQ Sustainable Entre Rios project in an agroecological perspective. It was used the participatory approach through analyzes of the sustainability indicators for agro ecosystems. The Participatory Rural Appraisal evidenced that the main source of income of the settlers is still wood and that most of the settlers who remain in Entre Rios make their living through external sources of income, such as retirement, rent of property in other areas, Bolsa Família. It is also common to find families where men have to do temporary jobs in near farms or in saw mills to complete the family income, as well as to invest in their own animal husbandry activities. The results is that most settlers abandon their land lots for lack of proper conditions, as an example, in the first semester of 2010, 3 families left the settlement in one of the settlement areas. The Cupuaçu family presented the best index of total sustainability ( SITotal = 2.09 ), owing to the diversity of activities allowing income generations, inside or outside the ranch, besides the intense involvement of the family with the Association, courses and exchange, contributed to this result. Considering the ecological sustainability, the availability of alternative productions practices, especially, apiculture, and agroforestry systems, were fundamental factors for the composition of higher indices. The Social sustainability indices have presented the worst performance among all indices, for every family, showing the lack of structure and the present abandonment situation that the settlers are exposed to. Besides the blocks in the production process, there is still the difficulty to access consumer markets, due to the distance and lack of transportation for the products. The results indicated that the settlement participation is vital to build projects that attend to their concrete needs and particularities. This participation can increase the adhesion in numbers and helps them to understand better their management process and development. It is necessary some actions in order to develop the diversified production food and not forest wooden products in ecological bases taking all productive environment. It seems important some actions in the agroecological transition process to guarantee the sustainability and improvement of the settlement lives quality. It will help to maintain the settlement people in their lands. The governmental institutions constraints and the gap of help jeopardize the settlement situation as a result there is an increasing in the region deforest and bonfire.